State Healthcare Paradoxes: Accessibility, Politics, and Public Health Challenges in Tehsil Kot Addu - Muhammad Abubakr; Dr. Majid Hussain Alias Ghalib Hussain; Danish Iqbal (`, 2025)
Pakistan is a nation with significant structural paradoxes in healthcare, where policy promises in the area of universal care fail to align with lived conditions. The article focuses on healthcare provision in Tehsil Kot Addu, Southern Punjab, in relation to accessibility, politics, and community health matters. According to a mixed-methods research design of surveys, interviews, and secondary data, the study determined that despite the presence of health facilities such as Basic Health Units (BHUs) and the Tehsil Headquarters Hospital (THQ), most are poorly funded, staffed, and geographically inaccessible. Political patronage is also a factor in health care provision because it is more likely that policies will focus on the areas with an electoral advantage rather than on the needs of the population. The public health issues of high maternal mortality, outbreaks of communicable diseases, and inadequate preventive medical care are manifestations of systemic neglect and rural disadvantage. The paper has named three availability versus accessibility, political visibility versus institutional absence, and preventative rhetoric versus curative reality paradoxes that characterize the healthcare environment in Kot Addu. These results indicate that health governance in rural areas should be enhanced, unequal resource distribution minimized, and concern should be focused on prevention to attain meaningful health disparities. keywords: Medical access, The patronage system, Health concerns, Rural health, State paradox, Kot Addu, Pakistan.